Trehalose induces antagonism towards Pythium debaryanum in Pseudomonas fluorescens ATCC 17400. - Gaballa, A (1997)
Pseudomonas fluorescens ATCC 17400 shows in vitro activity against Pythium debaryanum under conditions of iron limitation. A lacZ reporter gene introduced by transposon mutagenesis into the P. fluorescens ATCC 17400 trehalase gene (treA) was induced by a factor released by the phytopathogen Pythium debaryanum. The induction of the lacZ gene was lost upon treatment of the Pythium supernatant with commercial trehalase. A trehalose concentration as low as 1 microM could induce the expression of treA. The mutation did not affect the wild-type potential for fungus antagonism but drastically decreased the osmotolerance of the mutant in liquid culture and suppressed the ability of P. fluorescens ATCC 17400 to utilize trehalose as a carbon source. A subsequent transposon insertion in treP, one of the trehalose phosphotransferase genes upstream of treA, silenced the lacZ gene. This double mutant restricted fungal growth only under conditions of high osmolarity, which probably results in internal trehalose accumulation. These data confirm the role of the disaccharide trehalose in osmotolerance, and they indicate its additional role as an initiator of or a signal for fungal antagonism.